2019
DOI: 10.1249/jsr.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation and Its Contribution to Mood and Performance Deterioration in College Athletes

Abstract: Sleep deprivation is very common among collegiate student athletes, resulting in impacts on mood, physiology, and performance. There are multifactorial contributions to sleep deprivation, but resulting alterations in sleep architecture explain impacts on learning, vigilance, mood, and athletic performance. Recognition of the physical impacts is key. Clinical inquiry is warranted. Medication can be helpful short term but should be used with caution due to effects on sleep cycle and the potential for addiction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…Similar to pain hyperesthesia, sleep disturbances have been shown in the literature to have a significantly negative effect on mood. 37 , 38 , 39 , 40 A patient who is suffering from depressed mood, anxiety, or fatigue in addition to their FAIS can be potentially at a poorer outcome compared someone who is not. 41 Therefore, it is important in the FAIS population to identify these additional issues in order to facilitate optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to pain hyperesthesia, sleep disturbances have been shown in the literature to have a significantly negative effect on mood. 37 , 38 , 39 , 40 A patient who is suffering from depressed mood, anxiety, or fatigue in addition to their FAIS can be potentially at a poorer outcome compared someone who is not. 41 Therefore, it is important in the FAIS population to identify these additional issues in order to facilitate optimal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Less but similar information is available on the relationship between study timetables, sleep timing/length, and academic performance in university students ( Beşoluk et al, 2011 ; Li et al, 2018 ; Smarr and Schirmer, 2018 ). In addition, there are also studies on the effects of sleep deprivation on university students’ athletic performance and wellbeing ( Hodge et al, 2012 ; Bolin, 2019 ). A number of different initiatives/courses or interventions directed at either general or specific university students’ populations ( Tsai and Li, 2004 ; Brown et al, 2006 ; Trockel et al, 2011 ; Quan et al, 2013 ; Kloss et al, 2014 ; Ye and Smith, 2015 ; Levenson et al, 2016 ; Hershner and O’Brien, 2018 ) have shown encouraging results either in terms of increased sleep hygiene literacy ( Tsai and Li, 2004 ; Brown et al, 2006 ; Quan et al, 2013 ; Kloss et al, 2014 ; Ye and Smith, 2015 ; Hershner and O’Brien, 2018 ) or actual improvement in sleep habits and/or sleep quality ( Brown et al, 2006 ; Trockel et al, 2011 ; Levenson et al, 2016 ; Hershner and O’Brien, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are also studies on the effects of sleep deprivation on university students' athletic performance and wellbeing (Hodge et al, 2012;Bolin, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Less but similar information is available on the relationship between study timetables, sleep timing/length and academic performance in university students (Li et al, 2018, Beşoluk et al, 2011; Smarr and Schirmer, 2018). In addition, there are also studies on the effects of sleep deprivation on university students’ athletic performance and wellbeing (Hodge et al, 2012; Bolin, 2019).…”
Section: Introductionmentioning
confidence: 99%